Pengaruh Kepemilikan Manajerial terhadap Firm Performance melalui Dividend Policy sebagai Variabel Intervening di Indonesia pada Perusahaan yang Terdaftar dalam Bursa Efek Indonesia (BEI) - Adella Diastari; Devie Devie Devie (Business Accounting Review, 2017)
This study aimed to prove the effect of managerial ownership on firm performance and dividend policy, also the effect of managerial ownership on firm performance through dividend policy as an intervening variable. This study conducted on all sector of Indonesian listing companies that has done their Initial Public Offering at 2010 the latest, excluding financial sector. Final sample was made from 425 firm years. Managerial ownership was measured by percentage of managerial ownership, dividend policy was measured by dividend yield and dividend payout. On the other hand, firm performance was measured by both market method and accounting method, by using Tobin’s Q, ROA, and ROE.The final result shows that managerial ownership had a significant and negative influence towards both firm performance and dividend policy. But, dividend policy had a significant and positive influence on firm performance. While for managerial ownership by using dividend policy as intervening variable on firm performance had significant and negative influence. The result shows that managerial ownership was not suitable to be used in Indonesia to reduce agency problem and also not suitable to be applied based on the stewardship theory.